Convergence of Relative Prices and Inflation in Central and Eastern Europe - Holub, Tomas (IMF Working Papers; Working Paper ;, 2001)
The paper assesses inflation risks resulting from the convergence of structures of relative prices in Central and Eastern European (CEE) countries toward the European Union (EU). The basic idea of the paper is that under low downward flexibility of domestic nominal prices, the adjustment of relative price structures is likely to lead to higher inflation. The authors find that the degree of differences in the structures of relative prices in transition economies vis-a-vis EU economies has a strong negative relationship to price levels in the transition economies. Based on their calculations, the authors assess the likely future inflationary pressures that can stem from the remaining differences between the structures of relative prices in the CEE economies and the EU. The authors argue that their approach can be thought of as an extension of the standard Balassa-Samuelson explanation of international variability in price levels.